The controllable of BODIPY dimers without installing blocking groups as both fluorescence and singlet oxygen generators - Jianfang Cao; Tianci Zhang; Xinyu Chen; Xue Ma; Jiangli Fan (Smart Molecules)
Abstract We compared a range of BODIPY dimer derivatives without installing blocking groups by optimizing geometry structures and analyzing energies, frontier molecular orbitals, Chole&Cele map, electron density difference, spin‐orbit coupling (SOC) matrix and decay rate constants from excited states. The dihedral angles of the β‐β‐linked BODIPY dimer and the α‐α‐linked BODIPY dimer tend to flatten in the T1 state, which is detrimental to the occurrence of the intersystem crossing (ISC). Conversely, the dihedral angle of the meso‐β‐linked BODIPY dimer, the meso‐meso‐linked BODIPY dimer and α‐γ‐linked BODIPY dimer is within the range of 125°–143° in the T1 state, facilitating ISC and the generation of singlet oxygen. Notably, the transition from S1 to S0 involving lowest unoccupied molecular orbital to highest occupied molecular orbital with long‐wavelength emission and moderate oscillator strength underpins the remarkable long emission peaks observed experimentally for α‐γ‐linked BODIPY dimer. Moreover, the apparent SOC matrix enhances the ISC process, resulting in a respectable efficiency in generating singlet oxygen for this dimer. In meso‐β‐linked BODIPY, meso‐meso‐linked BODIPY, and α‐γ‐linked BODIPY, the S1→T1 process is characterized by a significant charge transfer, specifically transitioning from the 1CT state to the 3LE state, indicative of a spin‐orbit charge transfer ISC (SOCT‐ISC) mechanism. The ability to regulate the photosensitivity of BODIPY dimers by adjusting the dihedral angle between the two units in the T1 state unveils new avenues for designing high‐performance photosensitizers for both therapeutic and imaging applications.